On linear and planar discovery - Gečiauskas, E. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. Гячяускас. О линейном и плоском поисках E. Gečiauskas. Apie linijinę ir plokščią paieškas